2017
DOI: 10.1093/mnras/stx1887
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy formation with BECDM – I. Turbulence and relaxation of idealized haloes

Abstract: We present a theoretical analysis of some unexplored aspects of relaxed Bose-Einstein condensate dark matter (BECDM) haloes. This type of ultralight bosonic scalar field dark matter is a viable alternative to the standard cold dark matter (CDM) paradigm, as it makes the same large-scale predictions as CDM and potentially overcomes CDM's small-scale problems via a galaxy-scale de Broglie wavelength. We simulate BECDM halo formation through mergers, evolved under the Schrödinger-Poisson equations. The formed hal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
398
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 318 publications
(421 citation statements)
references
References 93 publications
20
398
3
Order By: Relevance
“…Using analytic tools, Hu, Barkana & Gruzinov (2000) showed that perturbations grow linearly on scales much larger than the Jeans scale at equality, kJeq = 9 m/10 −22 eV 1/2 Mpc −1 , but oscillate on smaller scales leading to a suppression of clustering power and the subsequent deficit of dwarf galaxies. BECDMonly numerical simulations confirmed this picture: modestresolution simulations verified the suppression of low-mass haloes (Woo & Chiueh 2009), while higher resolution simulations characterized the formation of solitonic cores (e.g., Schwabe, Niemeyer & Engels 2016a;Mocz et al 2017); although, we remark that these simulations did not use self-consistent initial conditions predicted by the BECDM model (Hlozek et al 2015), but artificial ones instead to highlight/exaggerate growth of structure. Simulations with WDM, although ignoring the quantum effects of BECDM, also serve as a guideline for understanding structure formation in BECDM.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Using analytic tools, Hu, Barkana & Gruzinov (2000) showed that perturbations grow linearly on scales much larger than the Jeans scale at equality, kJeq = 9 m/10 −22 eV 1/2 Mpc −1 , but oscillate on smaller scales leading to a suppression of clustering power and the subsequent deficit of dwarf galaxies. BECDMonly numerical simulations confirmed this picture: modestresolution simulations verified the suppression of low-mass haloes (Woo & Chiueh 2009), while higher resolution simulations characterized the formation of solitonic cores (e.g., Schwabe, Niemeyer & Engels 2016a;Mocz et al 2017); although, we remark that these simulations did not use self-consistent initial conditions predicted by the BECDM model (Hlozek et al 2015), but artificial ones instead to highlight/exaggerate growth of structure. Simulations with WDM, although ignoring the quantum effects of BECDM, also serve as a guideline for understanding structure formation in BECDM.…”
Section: Introductionmentioning
confidence: 77%
“…Here we outline the advantages and disadvantages of different methods (spectral, adaptive grid finite difference, and SPH and mesh-free finite-volume methods for the Madelung formulation). Spectral methods are an ideal choice for the Schrödinger-Poisson equations, owing to the smoothness of the wavefunction, and the unitary nature of the discretization (Mocz et al 2017). Spectral accuracy allows for machine-precision control of spatial truncation errors.…”
Section: Discussion Of Various Numerical Approaches For Becdm and Thementioning
confidence: 99%
See 2 more Smart Citations
“…for m ∈ Z. As noted in [3,19], we must choose a time step such that our unitary operators which evolve the system forward in time,…”
Section: Momentum Aliasingmentioning
confidence: 99%